Analisis Daya Saing Ekspor Lada Juga Pengaruhnya Bagi Cadangan Devisa di 5 negara Pengekspor Utama Lada (Studi Kasus Indonesia, Malaysia, Vietnam, Brazil dan India) - Nuriman Ramadhani; Murtala Murtala; Fanny Nailufar; Yurina Yurina (LPPM UNIMAL, 2020)
This study aims to analyze the level of export competitiveness of pepper and its effect on foreign exchange reserves in the 5 main exporting countries of pepper (a case study in Indonesia, Malaysia, Vietnam, Brazil, and India). The analysis model used is Revealed Comparative Advantage (RCA) and the Panel Autoregressive Distributed Lag (PARDL) method. The results of the analysis in this study with the RCA index show that Vietnam is the largest exporter of pepper with an RCA index value of 1.2631, followed by Brazil with an RCA value of 1.136. For countries, Indonesia, Malaysia, and India still below average competitiveness and still have to increase their pepper exports. Furthermore, the analysis using PARDL shows that in the long term, the pepper export has a positive and significant effect on foreign exchange reserves with probability (0.000 <0.05), but the pepper export has no positive and insignificant effect on foreign exchange reserves with the probability of 0.3577> 0.05).